Policy spillovers: The impact of foreign policy on domestic creation of green energy innovation - Andrin Spescha; Tobias Stucki; Martin Woerter (ETH Zurich, KOF Swiss Economic Institute, 2016)
In this paper, we investigate, based on a representative sample of Swiss and German firms, the impact of foreign green energy related policies on domestic innovation activities. Under control of the respective domestic policy stringency, we find a significant positive effect of foreign regulations, foreign voluntary agreements, and foreign public subsidies. However, when we introduce foreign (policy induced) demand, the significant effects of the other foreign policies vanish. Hence, we see that foreign policy impacts domestic innovation primarily from the demand side. We further find that foreign subsidies negatively affect domestic innovation activities of foreign owned firms operating in domestic. Finally, we find that foreign policies dampen the effect of national policy initiatives. Our results therefore call for an international coordination of policy initiatives to increase the effectiveness of the respective national policies. @In dieser Studie untersuchen wir, basierend auf einer repräsentativen Stichprobe bestehend aus Schweizer und Deutschen Firmen, den Einfluss von ausländischen Umweltpolitikmassnahmen auf die Innovationsaktivitäten von inländischen Firmen. Wir finden, unter Konstanthaltung der jeweiligen inländischen Politikmassnahmen, einen signifikant positiven Einfluss von ausländischer Regulierung, ausländischer Selbstverpflichtung und ausländischen Subventionen. Wenn wir jedoch ausländische Nachfrage als Kontrollvariable hinzufügen, verschwinden die signifikanten Effekte der ausländischen Politikmassnahmen fast vollständig. Wir schliessen daraus, dass ausländische Umweltpolitik die inländische Innovationsaktivität primär von der Nachfrageseite her stimuliert. Wir finden zudem, dass ausländische Subventionen die Innovationsaktivitäten von Firmen im Inland, die in ausländischem Besitz sind, negativ beeinflussen. Im Allgemeinen schwächen die ausländischen Politikmassnahmen den Effekt von inländischen Politikmassnahmen stark ab. Dieses Resultat hebt dieWichtigkeit von internationaler Koordination von Politikmassnahmen zur Steigerung derer Effektivität hervor.
Keywords: O30; O34; Q55; 330; Energy; innovation; policy; demand